A serpent's tooth [large type] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2013)
It's homecoming in Absaroka County, Wyoming, but the festivities are interrupted when a homeless boy wanders into town. A Mormon "lost boy," Cord Lynear is searching for his missing mother. Sheriff Longmire and companions Victoria Moretti and Henry Standing Bear embark on a high plains scavenger hunt to reunite mother and son. The trail leads to an interstate polygamy group that's harboring a stockpile of weapons and a vicious vendetta.